2017
DOI: 10.5194/acp-17-8923-2017
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation of sulfate aerosols at low relative humidity

Abstract: Abstract. Evaporation of sulfuric acid from particles can be important in the atmospheres of Earth and Venus. However, the equilibrium constant for the dissociation of H 2 SO 4 to bisulfate ions, which is the one of the fundamental parameters controlling the evaporation of sulfur particles, is not well constrained. In this study we explore the volatility of sulfate particles at very low relative humidity. We measured the evaporation of sulfur particles versus temperature and relative humidity in the CLOUD cham… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…The saturation vapour pressures of HOMs were calculated using SIM-POL (Pankow and Asher, 2008) as the method of Nanoolal et al (2008) produces unrealistic estimates of vapour pressures for multifunctional HOMs containing hydroperoxide or a peroxy acid group (Kurteìn et al, 2016). H 2 SO 4 was treated as a non-volatile condensing vapour, which generally is a reasonable assumption at typical atmospheric relative humidity and NH 3 levels (Tsagkogeorgas et al, 2017). The coagulation process, dry deposition process, and the dilution of aerosol number concentration caused by boundary layer evolution were estimated in the model as well.…”
Section: Model Descriptionsmentioning
confidence: 99%
“…The saturation vapour pressures of HOMs were calculated using SIM-POL (Pankow and Asher, 2008) as the method of Nanoolal et al (2008) produces unrealistic estimates of vapour pressures for multifunctional HOMs containing hydroperoxide or a peroxy acid group (Kurteìn et al, 2016). H 2 SO 4 was treated as a non-volatile condensing vapour, which generally is a reasonable assumption at typical atmospheric relative humidity and NH 3 levels (Tsagkogeorgas et al, 2017). The coagulation process, dry deposition process, and the dilution of aerosol number concentration caused by boundary layer evolution were estimated in the model as well.…”
Section: Model Descriptionsmentioning
confidence: 99%
“…Furthermore, NPF was found to be an important process inside the convective outflows (e.g. Twohy et al, 2002;Waddicor et al, 2012). From measurements in the upper troposphere it is commonly assumed that the occurrence of NPF is directly connected to deep-convective cloud systems (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the expression formulated by Tsagkogeorgas et al (2017) with the saturation vapour pressure psat of H2SO4 (above a flat surface) and with an accommodation coefficient of α = 0.65 (Pöschl et al, 1998), the ice particle's change of mass m per time unit is calculated by: In Figure B-1 the variability of two aspects is considered and in the panels (a-c) it is distinguished between three ice particle radii (1 µm, 10 µm, and 100 µm) and two different ice particle number concentrations (0.01 and 0.1 cm -3 ). The study by Ueyama et al (2020) revealed that ice particles (effective radii of about 15 µm) persist over 12 to 20 hours at convective outflow levels between 365 K and 370 K potential temperature in the 2017 AMA.…”
Section: Appendix B: Impact Of Ice Particles On Npf Precursors' Saturmentioning
confidence: 99%